Cytokeratin expression and distribution pattern of epithelioid macrophages in animals with different pathological forms of bovine paratuberculosis: potential role in resilience to PTB - Navarro León, Alejandra Isabel; Muñoz, Marta; Blanco-Vázquez, Cristina; Iglesias, Natalia; Iglesias, Tania; Canive, María; Badia-Bringué, Gerard; Alonso-Hearn, Marta; Balseiro, Ana; Casais, Rosa (Frontiers in Veterinary Science, 2025)
Paratuberculosis (PTB) is a chronic enteritis caused by Mycobacterium avium subsp. paratuberculosis (Map). Genome-wide association studies revealed a significant enrichment of the keratinization pathway in cattle with multifocal lesions, suggesting a potential role of cytokeratins (CKs) in PTB resilience mechanisms. To confirm this, the amount of CK-expressing cells was analyzed in granulomas from the distal jejunum (DJE) and jejunal lymph nodes (DJELN) of animals with focal, multifocal, and diffuse lesions, and in control animals without lesions. Quantitative double-immunohistochemical (D-IHC) analysis [using Iba1 (ionized calcium-binding adapter molecule-1) and CK, as specific markers of macrophages and epithelial cells, respectively] showed that animals with multifocal lesions had the highest numbers of double-Iba1/CK positive cells [epithelioid macrophages (EMs)]. Significant differences were observed with the focal (p < 0.001), diffuse (p = 0.038), and control groups (p < 0.001) in JELN. Similarly, these animals showed higher numbers of single-CK expressing cells in JELN and DJE. Two EM distribution patterns were observed. In Pattern 1, mostly observed in animals with multifocal lesions (low Map load, no clinical signs), EMs form a barrier-like arrangement around the granuloma, while in Pattern 2, mainly found in animals with diffuse lesions (high Map load, clinical signs), EMs have a diffuse arrangement throughout the granuloma. These findings suggest that animals with multifocal lesions might represent a resilient phenotype that controls Map infection and disease progression. This is achieved through the formation of ordered granulomas that prevent Map dissemination and maintain tissue integrity, which are characteristic features of resilient animals. CK could be considered a potential biomarker of PTB resilience.